IMAGE MEDIA AND THE RESULTS OF LEARNING OUTCOMES OF KONTRASTIVE KULTURKUNDE COURSES OF THE STUDENTS OF GERMAN LANGUAGE EDUCATION STUDY PROGRAM, FKIP PATTIMURA UNIVERSITY, AMBON - Tamaela Ida Costansa; Melanius Sarbunan (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2021)
The purpose of this study is to determine the influence of the use of image media on the learning outcomes of students of the German Language Education Study Program in Kontrastive Kulturkunde courses that use image media and those that do not use images. The use of image media applied in this study follows what Macaire and Hosch (2004: 67) have suggested about the function of images, that images can reactivate students' initial knowledge (Vorwissen der Schülerinnen und Schüler), show similarities/authenticity (Authentizität) and indicate actual situations (Aktualität), a communicative perspective image of an object and a representative image, which is a visual that depicts the state of nature and people's lives. (Perspektive und Repräsentativität) and which have similarities or differ with their own culture (Nähe oder Ferne zur eigenen Kultur). This research was motivated by the low learning outcomes of students in Kontrastive Kulturkunde courses. The type of this research used is experiment with one group pretest - posttest design with t-test analysis technique with significance level α = 0.05. Testing the effectiveness of this study is with the use of image media. The target of this study was 20 students of semester 4, German Language Education Study Program FKIP Pattimura University Ambon in Kontrastive Kulturkunde courses. The result of the calculation appears that, tcount > ttable=1,729 which is 11,103 > 1,729. Based on the results of the calculation it can be said that, there is a noticeable difference between the value after and before the application of the image media